2022
DOI: 10.1021/acsomega.1c05659
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing Nonspecific Binding in Biolayer Interferometry Experiments for Weak Ligand–Analyte Interactions

Abstract: Quantitative analysis of protein–protein interactions (PPIs) using biolayer interferometry (BLI) requires effective suppression of nonspecific binding (NSB) between analytes and biosensors. In particular, the study of weak interactions (i.e., K D > 1 μM) requires high concentrations of analytes, which substantially increases NSB. However, there are only a few so-called NSB blockers compatible with biomolecules, which limits the use of BLI in the accurate analysis of weak int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…After immobilizing CA121 HEX : 6HIS to the HIS‐affinity probes, we report the biochemical constants for cyFG‐3 are K D =0.963±0.06 μM, k on =8.90±0.53×10 3 M −1 s −1 , k off =8.58±0.136×10 −3 s −1 (Figure 6E). We confirmed our result with a cyclic peptide by carrying out a BLI assay with a positive control, a small molecule antiviral Lenacapvir (LEN) that was recently approved for use in highly treatment‐experienced individuals who are HIV‐1–positive and on a failing antiretroviral therapy (ART) regimen [34,38–42] . The biochemical constants for LEN to CA HEX : 6HIS are K D =28.6±0.2 nM, k on =1.040±0.007×10 4 M −1 s −1 , k off =2.978±0.015×10 −4 s −1 (Supplementary Figure S12).…”
Section: Resultssupporting
confidence: 73%
“…After immobilizing CA121 HEX : 6HIS to the HIS‐affinity probes, we report the biochemical constants for cyFG‐3 are K D =0.963±0.06 μM, k on =8.90±0.53×10 3 M −1 s −1 , k off =8.58±0.136×10 −3 s −1 (Figure 6E). We confirmed our result with a cyclic peptide by carrying out a BLI assay with a positive control, a small molecule antiviral Lenacapvir (LEN) that was recently approved for use in highly treatment‐experienced individuals who are HIV‐1–positive and on a failing antiretroviral therapy (ART) regimen [34,38–42] . The biochemical constants for LEN to CA HEX : 6HIS are K D =28.6±0.2 nM, k on =1.040±0.007×10 4 M −1 s −1 , k off =2.978±0.015×10 −4 s −1 (Supplementary Figure S12).…”
Section: Resultssupporting
confidence: 73%
“…We show, in particular, that the combination of BSA and trehalose exhibits good performance as a blocking agent. Although the significant bioactivity of nonspecifically bound BMP2 was an issue in our case, this study demonstrated the potential of biomaterials with bare glass in effectively retaining and delivering biologically active BMP2, as previously investigated [38] .…”
Section: Discussionsupporting
confidence: 58%
“…Trehalose, recognized for preventing protein aggregation, has been studied in particular for treating neurodegenerative diseases, such as Alzheimer’s and Huntington’s 37 . It also showed some interesting properties in BioLayer Interferometry studies as an additive for reducing non-specific binding 38 . Interestingly, a patent described using 5% trehalose to block functionalized surfaces, reducing serum protein adsorption 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal His 6 and SUMO-tagged NS1 proteins were used for immobilization. The buffer was 20 mM sodium phosphate (pH 7), 150 mM NaCl, 1% bovine serum albumin, and 0.6 M sucrose 56 . All reported values are the average and standard deviation of three repeated measurements.…”
Section: Methodsmentioning
confidence: 99%